Terapi Suportif Meningkatkan Motivasi untuk Melakukan Operasi Katarak pada Pasien Katarak di Wilayah Kerja Puskesmas Tempurejo Kabupaten Jember (Supportive Therapy to Increase Motivation to Undergo Cataract Surgery on Patients with Cataract in the Area of - Siswoyo Siswoyo; Murtaqib Murtaqib; Tri Buana Ratna Sari (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Cataract was an eye disease that could induce cloudy eye lens. The lack of motivation within innerself caused patients to be reluctant to undergo cataract removal surgery which could makeblindness rate keep increasing. Supportive therapy was a form of therapy used on individuals onpatients with difficulties in solving their problems. The purpose of this study was to analyze theeffects of supportive therapy on motivation to undergo cataract removal surgery on patients withcataract. This study used pre-experimental, one-group pre-test design. Sample-obtaining techniquewas purposive sampling with 15 patients. Supportive therapy was given in three meetings. The firstand second session were grouped together as one meeting with the duration of 30-35 minutes foreach session. The third and fourth session were grouped together as one meeting with the durationof 30-35 minutes for each session. Data were analyzed by using dependent t test and showed adifference between pre-test and post-test with p value = 0,001 (p value < 0,05). The result showedthat there was an effect of supportive therapy on motivation to undergo cataract removal surgery inpatients with cataract. This study suggests nurses to give supportive therapy to patients withphysical or psychological problem.Keywords: cataract, supportive therapy, motivation